Development of E-Modules Based On Mobile Learning Applications to Improve Students' Critical Thinking Skills in Science Subject - Uma'iyah, Nofita; Wahyuni, Sri; Nuha, Ulin (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Developing an E-module based on a mobile learning application is used to improve the critical thinking skills of junior high school science students. Objective: This research aims to develop products in e-modules based on mobile learning applications that are valid, practical, and effective. Methods: The research method used is the ADDIE development model, which includes five stages: analyzing, designing, developing, implementing, and evaluating. The data analysis techniques used are validation sheets for validity tests and observation sheets for learning implementation for practicality. And the N-gain test and student questionnaire to test effectiveness. Results: Based on the results of the data analysis conducted, e-modules based on mobile learning applications have obtained valid results with average validation scores from the three validators, namely 83%, e-modules based on mobile learning in learning are considered very practical as teaching materials in science learning in junior high school because they get an average score of 94%, e-modules based on mobile learning applications are also considered to have been effective and feasible to use as teaching materials during science learning in junior high school because they have used e-modules based on mobile learning applications, students' thinking skills increase with grades N-gain with a high score of 0.77 and student response with a score of 74% with a good category. Novelty:  Previous researchers have never done this research, which develops e-modules based on mobile learning applications to improve students' critical thinking skills.